Service Quality and Completion Time with Patient Trust - Herya Putra Dharma; Ratna Wardani; Agus Khoirul Anam; Andi Hayyun Abiddin (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The hospital is a health service provider facility where the health quality determines satisfaction of patient which has an impact on patient trust in health facilities. This study aimed to determine the effect of service quality and turnaround time on patient trust. This research is a quantitative study with a cross sectional approach. The research location was at Mardi Waluyo Hospital, Blitar City, with an outpatients as the study sample. Data collection was carried out using a questionnaire which was then analyzed using SPSS. The results of linear regression test indicated there was a positive and significant impact on service quality (0,00<0,05) of turnaround time. Quality of service and turnaround time have a positive and significant effect (0,03 < 0,05). However, the completion time with the patient's trust does not have a positive and significant effect (0,19>0,05). Quality of service has a positive and significant effect on patient trust (0,00<0,05). The conclusion of this study showed that quality of servicesperformed at Mardi Waluyo Hospital, Blitar City was influenced trust of patient.